2015
DOI: 10.1177/0107408314560325
|View full text |Cite
|
Sign up to set email alerts
|

Veilederes beveggrunner for å unnlate å gi ikke-bestått i praksisstudier til tross for at læringsutbyttene ikke er nådd

Abstract: Background: Many professional educations have element of practice in their educations. Any assessment scheme involves large uncertainties, and this will in particular be applicable in practice assessment. Studies show that students who do not meet the goals of a practice period pass anyway. Purpose: The purpose of the literature study is to describe what may lie at the core of those supervisors who allow underperforming students to pass in practice. Method: A systematic literature search was carried out in Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
6
0
7
Order By: Relevance
“…We proposed a model using exploratory factor analysis (EFA) to support dimensionality and interpretation of the factors. Then, we tested a four-factor model, based on the reviews of previous studies (Hauge, 2015;, in a confirmatory factor analysis (CFA) framework. The Stata software, version 15, was used to analyse the data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We proposed a model using exploratory factor analysis (EFA) to support dimensionality and interpretation of the factors. Then, we tested a four-factor model, based on the reviews of previous studies (Hauge, 2015;, in a confirmatory factor analysis (CFA) framework. The Stata software, version 15, was used to analyse the data.…”
Section: Discussionmentioning
confidence: 99%
“…Both Hauge (2015) and Hughes et al (2016) conducted a literature review to investigate the phenomenon Failing to Fail. Hughes et al (2016) suggested that failure to fail is an issue with complex facets and identified five factors related to the failure to fail: the difficulty of failing a student, the emotional process for nurse mentors, the need for confidence, unsafe student characteristics and the importance of university support.…”
mentioning
confidence: 99%
See 3 more Smart Citations